Manifestation tendencies of deep and surface learning of mathematics at KTU - Novikienė, Regina; Matiukaitė, Rasa (Lietuvos matematikos rinkinys, 2013)
Researchers [5] state that a gifted child is the one who early understood how to learn and applies analysis-based learning style. Therefore, the faculty to learn might be treated as the key factor of student’s success. The article seeks to examine how widely the strategy of deep learning is spread among the students of Kaunas University of Technology (KTU) and what external and internal factors impede the learning.
Keywords: deep learning; surface learning